Charts for the design of recuperators (Journal of Science and Technology, 2015)
This paper presents charts for the design of recuperators as an alternative to the heat exchanger design chart developed by the author in a previous paper (Ref. 2). The charts portray the relations between the Heat Exchanger Effectiveness and other basic design parameters